CRIMINAL RESPONSIBILITY FOR PEDOPHILIA UNDER GENERAL, TRADITIONAL AND ISLAMIC LAWS - Fitri Wahyuni; M. Rizqi Azmi; Riana Kesuma Ayu; Herdiansyah Herdiansyah (Universitas Syiah Kuala, 2022)
Pedophiles often engage in sexual interactions with underage children, whether it's